국내 갈락토스혈증 아동의 식생활 관리에 대한 주 보호자와 임상전문가의 인식 및 지원 요구도 조사 - 임서정; 서혜지; 김유리; 오지은; Seojeong Yim; Hyeji Seo; Yuri Kim; Jieun Oh (Journal of the Korean Society of Food Culture, 2022)
Galactosemia is a rare genetic metabolic disease caused by galactose and its metabolites generated during carbohydrate metabolism, which is relatively rare in Asian countries, including Korea. Patients with galactosemia should be treated with a galactose-restricted diet. However, information is lacking about the exact content of galactose in food, and dietary guidelines for patients with galactosemia in Korea. This study aims to recognize the difficulties faced by parents and clinical experts of patients with galactosemia, and understand their demands. Totally, 5 parents of children diagnosed with galactosemia and 5 clinical professionals participated in the focus group interviews. The parents’ interview focused on the daily life of the patient, which included diet and social difficulties. The clinical experts mainly answered about medical care, including the number and status of patients, and their suggestions for effective treatment. Most parents were worried about social isolation due to conflicts in the family as well as in society due to a lack of understanding of the disease. The clinical experts stated the absence of a disease management system as the greatest problem. An integrated support system for patients with galactosemia, which includes appropriate dietary guidelines by considering the domestic environment, is required.